Efficacy and safety of radiotherapy combined with atezolizumab plus bevacizumab in treating hepatocellular carcinoma with portal vein tumour thrombus: a study protocol. Issue 12 (15th December 2022) - Wang, Kang; Yu, Hong-Ming; Xiang, Yan-Jun; Cheng, Yu-Qiang; Ni, Qian-Zhi; Guo, Wei-Xing; Shi, Jie; Feng, Shuang; Zhai, Jian; Cheng, Shu-Qun
Abstract : Introduction: Vascular invasion and metastasis are poor prognostic factors in patients with hepatocellular carcinoma (HCC). The efficacy of available therapeutic regimens for unresectable HCC is not satisfactory in HCC with portal vein tumour thrombosis (PVTT). Therefore, this open-label, single-arm phase II clinical trial aims to investigate the efficacy and safety of radiotherapy combined with atezolizumab plus bevacizumab in treating HCC patients with PVTT. Methods and analysis: We plan to enrol patients diagnosed with unresectable HCC complicated by PVTT. Intensity-modulated radiotherapy (IMRT) combined with atezolizumab plus bevacizumab will be administered for treatment. Patients will initially receive radiotherapy, with each IMRT cycle lasting for 28 days and the total dose of tumour (DT) of 40 Gy/20 f/26 d. CT scan will be performed again, and the treatment plan will be reformulated after field constriction. The treatment will continue until the total DT is up to 54–56 Gy/27–28 f. The treatment with atezolizumab plus bevacizumab will be started at 3±1 days after the initiation of radiotherapy and will continue until unacceptable toxicity or disease progression. The primary endpoint is objective response rate (ORR), while the secondary endpoints include overall survival, disease control rate, progression-free survival, time to progression, duration of response and the rate of surgical conversions. Assuming an ORR of 47%, with a two-sided alpha error of 0.1, 90% power, and a 10% drop-out rate, the required number of evaluable patients is 42. Ethics and dissemination: This study will be conducted according to the standards of Good Clinical Practice and in compliance with the principles of the Declaration of Helsinki. The Ethics Committee of our Hospital has approved the protocol (EHBHKY2021-K-017). All participants are required to provide written informed consent. The results of the trial will be published in peer-reviewed journals and presented at international conferences. Trial registration number: ChiCTR2100049831.